ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
The dyshomeostasis of copper has been implicated in a variety of human diseases. However, the selective manipulation of copper flux at the subcellular organelle level remains challenging, which hinders the development of mechanism-guided therapeutic interventions for related diseases. We report a modular prochelator platform that integrates organelle-targeting ligands with stimuli-cleavable masking groups to unmask a conserved dithiocarbamate (DTC) chelating motif in situ, enabling precise depletion of exchangeable copper within the targeted subcellular compartment. In triple-negative breast cancer (TNBC) cells exhibiting elevated copper levels, the mitochondria-targeted, reactive oxygen species (ROS)-activatable prochelator DHU-Cuex5 mediates organelle-specific copper sequestration, resulting in selective cytotoxicity that is specifically reversible upon Cu 2 + supplementation. Quantitative mitochondrial profiling reveals that treatment with 1 µM DHU-Cuex5 for 12 h reduces cytochrome-c oxidase activity to approximately 40% of control levels, collapses mitochondrial membrane potential (ΔΨm), and disrupts oxidative phosphorylation, as evidenced by decreased oxygen consumption rate and ATP production. Transcriptomic analysis corroborates these observations, demonstrating downregulation of electron transport chain Complex IV and copper homeostasis-related genes, as well as activation of AMPK signaling and oxidative stress pathways. These systems-level changes are consistent with profound mitochondrial respiratory dysfunction. Intratumoral administration of DHU-Cuex5 inhibits xenograft tumor growth with favorable safety profiles.